Contribution Percentage Of Some Visual Functions and The Accuracy of Forehand Shot In Table Tennis - Abdul Amir, Haider (Journal of Physical Education, 2017)
The problem of the research lies in the weakness of table tennis athletes due to lack of performance accuracy. The importance of the research lies in finding a relationship between the variables and finding a contribution percentage between visual functions and the most used shot in table tennis. The researcher used the deceptive method. The subjects were (8) advance table tennis athletes. The data was collected and treated using proper statistical operations. The researcher concluded a significant correlation relationship as well as contribution percentage between visual functions and the accuracy of shooting in table tennis. Finally the researcher recommended the necessity of paying attention to visual functions on other sports and other subjects.